Obesogenic eating behaviour and dietary intake in German children and adolescents: results from the GINIplus and LISA birth cohort studies - Marb, Anne; Libuda, Lars; Standl, Marie; Koletzko, Sibylle; Bauer, Carl-Peter; Schikowski, Tamara; Berdel, Dietrich; von Berg, Andrea; Herberth, Gunda; Bühlmeier, Judith; Harris, Carla P. (European Journal of Clinical Nutrition)
Abstract Background/objectives The transition to adolescence is characterised by considerable behavioural changes, including diet. This study describes the level of obesogenic eating behaviours in 10- and 15-year-olds, and their association with dietary intake. Subjects/methods Participants of the 10- and 15-year follow-ups of the German GINIplus and LISA birth cohort studies were included (N 10 = 2257; N 15 = 1880). Eating behaviours and dietary intake were assessed via self-report questionnaires. Sex-stratified, cross-sectional associations of “external eating”, “emotional eating” and “dietary restraint” (the latter at age 15 years only) with dietary intake (17 food groups—categorised into tertiles, macronutrients, and total energy) were assessed using multinomial logistic or multiple linear regression as required, adjusting for covariates and correcting for multiple testing. Results Reported levels of eating behaviours were low in both age-groups. External eating was higher in 10-year-old males than females, while all eating behaviours were most pronounced in 15-year-old females. At 10 years, emotional eating was associated with medium vegetable intake in females (Relative Risk Ratio (RRR) = 1.84, p = 0.0017). At 15 years, external eating was associated with total energy (kJ) in females ( β = 718, p = 0.0002) and high butter intake in males (RRR = 1.96, p = 0.0019). Dietary restraint in females was inversely associated with total energy ( β = −967, p < 0.0001) and omega-3 fatty acids (Means Ratio (MR) = 0.94, p = 0.0017), and positively associated with high fruit (RRR = 2.20, p = 0.0003) and whole grains (RRR = 1.94, p = 0.0013). Conclusion Obesogenic eating behaviour scores are low among children and adolescents of a predominantly high socioeconomic status population and present only few associations with specific aspects of diet, mainly among adolescent females.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Selective Area Growth of Cubic Gallium Nitride in Nanoscopic Silicon Dioxide Masks - Meier, Falco; Littmann, Mario; Bürger, Julius; Riedl, Thomas; Kool, Daniel; Lindner, Jörg; Reuter, Dirk; As, Donat Josef (physica status solidi (b))
Keywords: Condensed Matter Physics; Electronic; Optical and Magnetic Materials

Sixteen-week multicentre randomised controlled trial to study the effect of the consumption of an oat beta-glucan-enriched bread versus a whole-grain wheat bread on glycaemic control among persons with pre-diabetes: a study protocol of the CarbHealth study - Hjorth, Therese; Schadow, Alena; Revheim, Ingrid; Spielau, Ulrike; Thomassen, Lise M; Meyer, Klara; Piotrowski, Katja; Rosendahl-Riise, Hanne; Rieder, Anne; Varela, Paula; Lysne, Vegard; Ballance, Simon; et al. (BMJ Open)
Introduction In 2012, the estimated global prevalence of pre-diabetes was 280 million, and the prevalence is expected to rise to 400 million by 2030. Oat-based foods are a good source of beta-glucans, which have been shown to lower postprandial blood glucose. Studies to evaluate the effectiveness of the long-term intake of beta-glucan-enriched bread as part of a habitual diet among individuals with pre-diabetes are needed. Therefore, we designed a multicentre intervention study in adults with pre-diabetes to investigate the effects of consumption of an oat-derived beta-glucan-enriched bread as part of a normal diet on glycated haemoglobin (HbA1c) in comparison to consumption of whole-grain wheat bread. Methods and analysis The CarbHealth trial is a multicentre double-blind randomised controlled 16-week dietary intervention trial in participants 40–70 years of age with a body mass index of ≥27 kg/m 2 and HbA1c of 35–50 mmol/mol. The study is conducted at four universities located in Norway, Sweden and Germany and uses intervention breads specifically designed for the trial by Nofima AS. The aim is to recruit 250 participants. The primary outcome is the difference in HbA1c between the intervention and the control groups. The main analysis will include intervention group, study centre and baseline HbA1c as independent variables in an analysis of covariance model. Ethics and dissemination The study protocol was approved by respective ethical authorities in participating countries. The results of the study will be communicated through publication in international scientific journals and presentations at (inter)national conferences. Trial registration number NCT04994327 .
Keywords: General Medicine

Correction: Short-term effects of carbohydrates differing in glycemic index (GI) consumed at lunch on children's cognitive function in a randomized crossover study. - Jansen, K; Tempes, J; Drozdowska, A; Gutmann, M; Falkenstein, M; Buyken, Anette; Libuda, Lars; Rudolf, H; Lücke, T; Kersting, M (Eur J Clin Nutr)

Health relevance of lowering postprandial glycaemia in the paediatric population through diet': results from a multistakeholder workshop. - Vinoy, S; Goletzke, J; Rakhshandehroo, M; Schweitzer, L; Flourakis, M; Körner, A; Alexy, U; van Schothorst, EM; Ceriello, A; Zakrzewski-Fruer, JK; Buyken, Anette (Eur J Nutr)

The adrenal steroid profile in adolescent depression: a valuable bio-readout? - Hirtz, Raphael; Libuda, Lars; Hinney, Anke; Föcker, Manuel; Bühlmeier, Judith; Holterhus, Paul-Martin; Kulle, Alexandra; Kiewert, Cordula; Hauffa, Berthold P.; Hebebrand, Johannes; Grasemann, Corinna (Translational Psychiatry)
Abstract There is preliminary evidence that adrenal steroids other than cortisol may be valuable biomarkers for major depressive disorder (MDD). So far, studies have been conducted in adults only, and conclusions are limited, mainly due to small sample sizes. Therefore, the present study assessed whether adrenal steroids serve as biomarkers for adolescent MDD. In 261 depressed adolescents (170 females) treated at a single psychiatric hospital, serum adrenal steroids (progesterone, 17-hydroxyprogesterone, 21-deoxycortisol, 11-deoxycortisol, cortisol, cortisone, deoxycorticosterone, corticosterone) were determined by liquid chromatography-tandem mass spectrometry. Findings were compared to that of an age- and sex-matched reference cohort ( N = 255) by nonparametric analysis of variance. Nonparametric receiver operating characteristics (ROC) analyses were conducted to evaluate the diagnostic performance of single steroids and steroid ratios to classify depression status. Sensitivity analyses considered important confounders of adrenal functioning, and ROC results were verified by cross-validation. Compared to the reference cohort, levels of deoxycorticosterone and 21-deoxycortisol were decreased ( P < 0.001). All other glucocorticoid- and mineralocorticoid-related steroids were increased ( P < 0.001). The corticosterone to deoxycorticosterone ratio evidenced excellent classification characteristics, especially in females (AUC: 0.957; sensitivity: 0.902; specificity: 0.891). The adrenal steroid metabolome qualifies as a bio-readout reflecting adolescent MDD by a distinct steroid pattern that indicates dysfunction of the hypothalamus–pituitary–adrenal axis. Moreover, the corticosterone to deoxycorticosterone ratio may prospectively qualify to contribute to precision medicine in psychiatry by identifying those patients who might benefit from antiglucocorticoid treatment or those at risk for recurrence when adrenal dysfunction has not resolved.
Keywords: Biological Psychiatry; Cellular and Molecular Neuroscience; Psychiatry and Mental health

Emotionale Erfahrungen von Lehramtsstudierenden bei der Arbeit mit Eigenvideografien von Unterricht – Fallanalysen aus einer längsschnittlichen Interviewstudie im Praxissemester - Pollmeier, Pascal; Rogge, Tim; Vogelsang, Christoph (ZeHf – Zeitschrift für empirische Hochschulforschung)
Die Arbeit mit Videografien eigenen Unterrichts wird in Praxisphasen in der universitären Lehramtsausbildung zunehmend als methodisches Mittel zur Reflexion von Unterrichtserfahrungen genutzt. Als wesentlicher Einflussfaktor für einen erfolgreichen Einsatz werden dabei die begleitenden Emotionen der Studierenden angenommen. In einer längsschnittlichen Interviewstudie wurden daher die emotionalen Prozesse von 20 Lehramtsstudierenden bei der Arbeit mit Eigenvideografien in Begleitveranstaltungen des Praxissemesters untersucht. Dabei konnten drei Typen rekonstruiert werden, die prototypische emotionale Muster im Praxissemesterverlauf beschreiben, die durch die Valenz emotionaler Zustände bezüglich der Eigenvideografie zu Beginn und Ende des Praxissemesters charakterisiert werden können (negativ-positiv, positiv-positiv, negativ-negativ). Bei fallübergreifender Betrachtung konnten zudem zentrale Zusammenhänge zwischen Emotionen und Merkmalen des Videoeinsatzes identifiziert werden, wie die Vertrautheit mit Mitstudierenden, der Prozess der Aufnahmegenehmigung und Vorerfahrungen mit Eigenvideografie. Die Ergebnisse der Studie können zur Vermeidung intensiver negativer Emotionen bei der Nutzung videobasierter Reflexion eigenen Unterrichts beitragen und die Akzeptanz von Eigenvideografie zur eigenen Professionalisierung in der Lehrerbildung erhöhen.

Entwicklung von Unterrichtsplanungsfähigkeit im Fach Physik: Welchen Einfluss hat Professionswissen? - Riese, Josef; Vogelsang, Christoph; Schröder, Jan; Borowski, Andreas; Kulgemeyer, Christoph; Reinhold, Peter; Schecker, Horst (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im Lehramtsstudium sollen Studierende grundlegende Fähigkeiten zur theoriegeleiteten Unterrichtsplanung erwerben. In Übereinstimmung mit Modellen zur professionellen Handlungskompetenz von Lehrkräften wird hierbei meist angenommen, dass das im Studienverlauf erworbene Professionswissen eine wesentliche Grundlage für den Aufbau von Fähigkeiten zur Unterrichtsplanung bildet. Lerngelegenheiten zur Anwendung dieses Professionswissens bieten vor allem schulpraktische Phasen im fortgeschrittenen Studienverlauf. Es wird aber ebenso angenommen, dass gerade Erfahrungen mit der Unterrichtsplanung den Aufbau von Professionswissen unterstützen. Der Zusammenhang zwischen dem Ausmaß des Professionswissens und der Entwicklung von Planungsfähigkeit ist bisher unzureichend empirisch geklärt. Eine besondere methodische Herausforderung besteht darin, Planungsfähigkeiten sowohl möglichst authentisch als auch auf standardisierte Weise zu erfassen. Zur Untersuchung des genannten Zusammenhangs wurde eine längsschnittliche Studie im Prä-Post-Design bei angehenden Physiklehrkräften ( N = 68 im Längsschnitt) an vier Universitäten durchgeführt. Die Unterrichtsplanungsfähigkeit wurde mit Hilfe eines standardisierten Performanztests vor und nach dem Absolvieren eines Praxissemesters erfasst, indem als Standardsituation der Entwurf einer Unterrichtsstunde zum 3. Newton’schen Axiom unter definierten Zeitvorgaben im Praxissemester simuliert wurde. Zusätzlich wurden das fachliche, fachdidaktische und pädagogische Wissen der Studierenden mit Hilfe standardisierter Instrumente zu beiden Zeitpunkten erhoben, sowie die einschlägigen Lerngelegenheiten im Praxissemester über einen Fragebogen erfasst. Sowohl für Unterrichtsplanungsfähigkeit als auch für alle Wissensvariablen können Zuwächse im Praxissemester beobachtet werden. Cross-Lagged-Panel-Analysen zeigen, dass insbesondere die Ausprägung des fachdidaktischen und pädagogischen Wissens der Studierenden am Beginn des Praxissemesters die Entwicklung von Unterrichtsplanungsfähigkeit begünstigt.
Keywords: Education

Nutzungsverhalten von Lehrkräften bei der Implementierung einer physikdidaktisch innovativen Unterrichtskonzeption - Breuer, Judith; Vogelsang, Christoph; Reinhold, Peter (Zeitschrift für Didaktik der Naturwissenschaften)
Zusammenfassung Eine zentrale Aufgabe fachdidaktischer Forschung stellt die Verbesserung schulischen Unterrichts dar. Die freie Bereitstellung wirksamer Unterrichtskonzeptionen zur Unterstützung des Selbststudiums von Lehrkräften bildet eine Strategie für eine flächendeckende Implementierung fachdidaktischer Innovationen. Allerdings etablieren sich zahlreiche, empirisch erfolgreich evaluierte Unterrichtskonzeptionen nicht nachhaltig an Schulen. Daher untersucht das vorliegende Forschungsvorhaben den Implementationsprozess solcher Materialien unter authentischen Bedingungen. Dazu wurde kriteriengeleitet eine evidenzbasierte, fachdidaktisch innovative Unterrichtskonzeption ausgewählt: das Münchener Unterrichtskonzept zur Quantenmechanik (MILQ). Diese wurde den teilnehmenden Lehrkräften fakultativ zur Verfügung gestellt. Mittels Fallstudien wurde die Implementierung von MILQ von elf Lehrkräften durch halbstandardisierte Interviews zu Beginn und am Ende einer Unterrichtsreihe zur Quantenmechanik sowie zwei Unterrichtsbeobachtungen mit je einem anschließenden stimulated recall explorativ erfasst. Die Probanden setzten sich überwiegend heuristisch mit MILQ auseinander und implementierten vor allem Elemente auf Sichtstrukturebene im Unterricht, die konform zu ihren bisherigen Vorstellungen waren. Dadurch wurde das fachdidaktische Innovationspotential nicht ausgeschöpft. Bezeichnend ist, dass der empirische Wirksamkeitsnachweis von MILQ für die Beurteilung der Lehrkräfte nicht relevant war, was aus theoretischer Sicht bislang als ein zentrales Argument der Bereitstellungsstrategie zur Implementierung fachdidaktischer Innovation angenommen wurde.
Keywords: General Medicine

Learning to Plan by Learning to Reflect?—Exploring Relations between Professional Knowledge, Reflection Skills, and Planning Skills of Preservice Physics Teachers in a One-Semester Field Experience - Vogelsang, Christoph; Kulgemeyer, Christoph; Riese, Josef (Education Sciences)
Following concepts describing lesson planning as a form of anticipatory reflection, preservice physics teachers’ reflection skills are assumed to be positively connected with their planning skills. However, empirical evidence on this is scarce. To explore how relations between these specific skills change over the course of a field experience controlling for influences of professional knowledge, we conduct a pre-post field study with N = 95 preservice physics teachers in a one-semester field experience. Content knowledge (CK) and pedagogical content knowledge (PCK) (paper-and-pencil tests), and reflection and planning skills (standardized performance assessments) were assessed before and after the field experience. Path analyses revealed almost no influence of reflection skills on planning skills. Reflections skills did not contribute to preservice teachers planning skills beyond knowledge, indicating both constructs might represent rather independent abilities. The results show the need for further development of models describing the development of teachers’ professional knowledge and skills in academic teacher education and for the development of concepts for a better integration of reflection and lesson planning in field experiences.
Keywords: Public Administration; Developmental and Educational Psychology; Education; Computer Science Applications; Computer Science (miscellaneous); Physical Therapy; Sports Therapy and Rehabilitation

How to Teach a Teacher: Challenges and Opportunities in Physics Teacher Education in Germany and the USA - Van Dusen, Ben; Vogelsang, Christoph; Taylor, Joseph; Cauet, Eva (Physics Education)

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Changes In Eeg Microstate Patterns Following Exhaustive Treadmill Exercise When Employing Reduced Channel Resolution - Büchel, Daniel; Allen, Carlos; Lehmann, Tim; Sandbakk, Øyvind; Baumeister, Jochen (Medicine &Science in Sports& Exercise)
Keywords: Physical Therapy; Sports Therapy and Rehabilitation; Orthopedics and Sports Medicine

Hydrogel-Based Biosensors - Völlmecke, Katharina; Afroz, Rowshon; Bierbach, Sascha; Brenker, Lee Josephine; Frücht, Sebastian; Glass, Alexandra; Giebelhaus, Ryland; Hoppe, Axel; Kanemaru, Karen; Lazarek, Michal; Rabbe, Lukas; Song, Longfei; et al. (Gels)
There is an increasing interest in sensing applications for a variety of analytes in aqueous environments, as conventional methods do not work reliably under humid conditions or they require complex equipment with experienced operators. Hydrogel sensors are easy to fabricate, are incredibly sensitive, and have broad dynamic ranges. Experiments on their robustness, reliability, and reusability have indicated the possible long-term applications of these systems in a variety of fields, including disease diagnosis, detection of pharmaceuticals, and in environmental testing. It is possible to produce hydrogels, which, upon sensing a specific analyte, can adsorb it onto their 3D-structure and can therefore be used to remove them from a given environment. High specificity can be obtained by using molecularly imprinted polymers. Typical detection principles involve optical methods including fluorescence and chemiluminescence, and volume changes in colloidal photonic crystals, as well as electrochemical methods. Here, we explore the current research utilizing hydrogel-based sensors in three main areas: (1) biomedical applications, (2) for detecting and quantifying pharmaceuticals of interest, and (3) detecting and quantifying environmental contaminants in aqueous environments.
Keywords: Polymers and Plastics; Organic Chemistry; Biomaterials; Bioengineering

Hyphenation of ultra-high-performance liquid chromatography and ion mobility mass spectrometry for the analysis of sequence-defined oligomers with different functionalities and tacticity - Berg, Marie-Theres; Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
In recent years, sequence-defined oligomers (SDOs) gained increasing interest due to their perfectly controlled molecular structure, thus providing defined properties. In order to tune the properties, different functionalities need to be incorporated into the oligomers and the chain tacticity needs to be controlled. Beside the synthesis of SDOs, suitable methods need to be found to analyze the molecular structure. In this work, oligomers exhibiting an alternating or block-wise sequence of side chain functionalities were analyzed using a hyphenation of ultra-high-performance liquid chromatography and electrospray ionization mass spectrometry enhanced by ion mobility separation (IMS). Moieties in the side chains were varied according to polarity and bulkiness. Moreover, chain tacticity was varied. Drift times in the IMS cell and the corresponding collision cross section (CCS) values were shown to be individual parameters allowing the identification of SDOs, even in the case that SDO structures only differ in sequence or tacticity of side chain functionalities. Thus, a library of CCS values was obtained as reference used for the analysis of complex mixtures of SDOs.
Keywords: Ultra-high-performance liquid chromatography; ion mobility separation; mass spectrometry; LC-MS hyphenation; sequence-defined oligomers

Quinuclidine-Immobilized Porous Polymeric Microparticles as a Compelling Catalyst for the Baylis–Hillman Reaction - Kumar, Amit; Kuckling, Dirk; Nebhani, Leena (ACS Applied Polymer Materials)
Poly(quinuclidin-3-yl methacrylate-co-divinylbenzene) microparticles having porous as well as nonporous morphology and varying contents of quinuclidine functionality were synthesized by distillation–precipitation polymerization. Further, the synthesized microparticles were explored to catalyze the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Porous and nonporous microparticles functionalized with a catalytic moiety with a loading of 70% (labeled as P70 and NP70) were employed to optimize reaction parameters such as water content, solvent, and temperature for the Baylis–Hillman reaction between 4-nitrobenzaldehyde and acrylonitrile. Using optimal conditions, the catalytic efficiency of porous and nonporous microparticles at different feed compositions was determined. Porous microparticles containing 70% of quinuclidine (P70) displayed 100% conversion within 16 h at 50 °C, while nonporous microparticles containing 70% of quinuclidine (NP70) displayed a relatively less catalytic conversion, which is attributed to their lower surface area. Furthermore, the catalytic activity of porous microparticles containing 70% of quinuclidine (P70) for the Baylis–Hillman reaction involving a variety of aryl aldehyde derivatives was determined, where the microparticles displayed impressive catalytic efficiency. In addition, the reusability of the microparticles functionalized with a catalytic moiety was evaluated for five cycles of catalytic reaction.
Keywords: distillation−precipitation polymerization; porous microparticles; heterogeneous catalysis Baylis−Hillman reaction; reusable catalyst

Branching analysis of β-cyclodextrin-based poly(N-isopropylacrylamide) star polymers using triple detection SEC - Herberg, Artjom; Kuckling, Dirk (International Journal of Polymer Analysis and Characterization)
For the first time, poly(N-isopropylacrylamide) (PNIPAAm) star polymers with a β-cyclodextrin core are characterized in detail by size-exclusion chromatography (SEC) with triple detection to experimentally verify the number of arms. A combination of a refractive index detector, multi-angle laser light scattering detector, and an online-viscosimeter was used for branching analysis. At first, the SEC system was calibrated and the detector setup was validated using linear polystyrene reference polymers. The applicability of the established triple detection SEC for branching analysis was shown by the analysis of two commercially available polystyrene star polymers. Due to the high molar masses of the star polymers, both the contraction ratio g and g′ could be determined independently, thus allowing the calculation of the viscosity shielding ratio ε. Finally, the branching analysis of the PNIPAAm star polymers could experimentally confirm the assumed arm number of up to 21 arms. Moreover, an increasingly compact molecular structure and the influence of the arm number on the viscosity shielding ratio could be shown.
Keywords: Size-exclusion chromatography; triple detection; branching analysis; star polymers; poly(N-isopropylacrylamide); β-cyclodextrin

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Wie können Erklärvideos zum Erwerb physikalischen Konzeptwissens beitragen? - Hörnlein, Madeleine; Kulgemeyer, Christoph

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine

Zur Erinnerung: Warum Bildung für Lebensführung immer eine politische Dimension hat. Das Beispiel Nationalsozialismus - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Konzepte von Qualität in ihrer Bedeutung für Konsumentscheidungen verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Ressourcen für die Lebensgestaltung verstehen - Schlegel-Matthies, Kirsten; Methfessel, Barbara (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten; Bartsch, Silke; Brandl, Werner; Methfessel, Barbara

Die Bedeutung von Ressourcen für Lebensqualität und gesellschaftliche Teilhabe - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Lebensführung und Umgang mit Diversität– Haushaltswissenschaftliche Perspektiven - Schlegel-Matthies, Kirsten (Haushalt in Bidlung und Forschung)

Die Organisation der Daseinsvorsorge für die private Lebensführung reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lehren gestalten – Lernen ermöglichen. Fachdidaktische Hinweise - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Lebensweise, Lebensführung und Lebensstile reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung zwischen Wissenschaft und Lebenswelt - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung von Konsumentscheidungen für die Lebensführung analysieren und reflektieren - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Die Bedeutung und Funktion des Rechts für die Lebensführung verstehen - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Ernährungs- und Verbraucherbildung - Schlegel-Matthies, Kirsten (Konsum - Ernährung - Gesundheit. Grundlagen der Ernährungs- und Verbraucherbildung)

Information extraction in photon-counting experiments - Schapeler, Timon; Bartley, Tim (Physical Review A)

Laser-lithographically written micron-wide superconducting nanowire single-photon detectors - Protte, Maximilian; Verma, Varun B; Höpker, Jan Philipp; Mirin, Richard P; Woo Nam, Sae; Bartley, Tim (Superconductor Science and Technology)
Abstract We demonstrate the fabrication of micron-wide tungsten silicide superconducting nanowire single-photon detectors on a silicon substrate using laser lithography. We show saturated internal detection efficiencies with wire widths ranging from 0.59 µ m to 1.43 µ m under illumination at 1550 nm. We demonstrate both straight wires, as well as meandered structures. Single-photon sensitivity is shown in devices up to 4 mm in length. Laser-lithographically written devices allow for fast and easy structuring of large areas while maintaining a saturated internal efficiency for wire widths around 1 µ m.
Keywords: Materials Chemistry; Electrical and Electronic Engineering; Metals and Alloys; Condensed Matter Physics; Ceramics and Composites

Cryogenic integrated spontaneous parametric down-conversion - Lange, Nina Amelie; Höpker, Jan Philipp; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Optica)
Keywords: Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Cryogenic electro-optic modulation in titanium in-diffused lithium niobate waveguides - Thiele, Frederik; vom Bruch, Felix; Brockmeier, Julian; Protte, Maximilian; Hummel, Thomas; Ricken, Raimund; Quiring, Viktor; Lengeling, Sebastian; Herrmann, Harald; Eigner, Christof; Silberhorn, Christine; Bartley, Tim (Journal of Physics: Photonics)
Abstract Lithium niobate is a promising platform for integrated quantum optics. In this platform, we aim to efficiently manipulate and detect quantum states by combining superconducting single photon detectors and modulators. The cryogenic operation of a superconducting single photon detector dictates the optimisation of the electro-optic modulators under the same operating conditions. To that end, we characterise a phase modulator, directional coupler, and polarisation converter at both ambient and cryogenic temperatures. The operation voltage <?CDATA $V_{π/2}$?> V π / 2 of these modulators increases, due to the decrease in the electro-optic effect, by 74% for the phase modulator, 84% for the directional coupler and 35% for the polarisation converter below 8.5 <?CDATA $\,K$?> K . The phase modulator preserves its broadband nature and modulates light in the characterised wavelength range. The unbiased bar state of the directional coupler changed by a wavelength shift of 85 <?CDATA $\,nm$?> n m while cooling the device down to 5 <?CDATA $\,K$?> K . The polarisation converter uses periodic poling to phasematch the two orthogonal polarisations. The phasematched wavelength of the utilised poling changes by 112 <?CDATA $\,nm$?> n m when cooling to 5 <?CDATA $\,K$?> K .
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Opto-electronic bias of a superconducting nanowire single photon detector using a cryogenic photodiode - Thiele, Frederik; Hummel, Thomas; Protte, Maximilian; Bartley, Tim (APL Photonics)
Superconducting Nanowire Single Photon Detectors (SNSPDs) have become an integral part of quantum optics in recent years because of their high performance in single photon detection. We present a method to replace the electrical input by supplying the required bias current via the photocurrent of a photodiode situated on the cold stage of the cryostat. Light is guided to the bias photodiode through an optical fiber, which enables a lower thermal conduction and galvanic isolation between room temperature and the cold stage. We show that an off-the-shelf InGaAs–InP photodiode exhibits a responsivity of at least 0.55 A/W at 0.8 K. Using this device to bias an SNSPD, we characterize the count rate dependent on the optical power incident on the photodiode. This configuration of the SNSPD and photodiode shows an expected plateau in the single photon count rate with an optical bias power on the photodiode above 6.8 µW. Furthermore, we compare the same detector under both optical and electrical bias, and show there is no significant changes in performance. This has the advantage of avoiding an electrical input cable, which reduces the latent heat load by a factor of 100 and, in principle, allows for low loss RF current supply at the cold stage.
Keywords: Computer Networks and Communications; Atomic and Molecular Physics; and Optics

Nano-FTIR and chemical force analysis of electrografted aryldiazonium salts on ODT-microcontact printed Au-surfaces - Su, Jiangling; González Orive, Alejandro; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Oxidation stability of chromium aluminum oxynitride hard coatings - Bobzin, K.; Kalscheuer, C.; Grundmeier, Guido; de los Arcos, T.; Kollmann, S.; Carlet, M. (Surface and Coatings Technology)
Keywords: Materials Chemistry; Surfaces; Coatings and Films; Surfaces and Interfaces; Condensed Matter Physics; General Chemistry

Thin Organic‐Inorganic Anti‐Fouling Hybrid‐Films for Microreactor Components - Neßlinger, Vanessa; Welzel, Stefan; Rieker, Florian; Meinderink, Dennis; Nieken, Ulrich; Grundmeier, Guido (Macromolecular Reaction Engineering)
Keywords: Polymers and Plastics; General Chemical Engineering; General Chemistry

Remote epitaxy of In(x)Ga(1-x)As(001) on graphene covered GaAs(001) substrates - Henksmeier, Tobias; Schulz, Johann Friedemann; Kluth, Elias; Feneberg, Martin; Goldhahn, Rüdiger; Sanchez, Ana M.; Voigt, Markus; Grundmeier, Guido; Reuter, Dirk (Journal of Crystal Growth)

Surface Instability Modulates Cortical Information Processing In Multi-Joint Compound Movements - Lehmann, Tim; Visser, Anton; Havers, Tim; Büchel, Daniel; Baumeister, Jochen

Professionalitätsentwicklung angehender Lehrkräfte - Kirsch, Alexander

Kooperatives Unterrichten von Studierenden des Lehramts an Grund- und Förderschulen als Vorbereitung auf den inklusiven naturwissenschaftlichen Sachunterricht - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Kirsch, Alexander; Blumberg, Eva; Schwab, Susanne (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Messung von Unterrichtsplanungskompetenz im Fach Sachunterricht: Empirische Befunde zur Kompetenzentwicklung angehender Grundschullehrkräfte auf Grundlage einer mehrdimensionalen Kompetenzstruktur - Kirsch, Alexander (Zeitschrift für Erziehungswissenschaft)
Zusammenfassung Im vorliegenden Beitrag werden nach ausführlicher theoretischer Diskussion des Kompetenzbegriffs und der Definition von Kompetenz als Können ein Modell sachunterrichtlicher Planungskompetenz sowie ein daran anschließendes Messinstrument vorgestellt. Im Hinblick auf den Einsatz dieses Instrumentes im Rahmen einer Evaluation des nordrhein-westfälischen Praxissemesters stellen sich Fragen nach der psychometrischen Struktur der Testauswertung. Da das Instrument sowohl zur Testung von Sachunterrichtsstudierenden mit dem Lehramtsprofil ‚Grundschule‘ als auch von Sachunterrichtsstudierenden mit sonderpädagogischem Schwerpunkt eingesetzt werden soll, ist zu zeigen, dass die Testergebnisse nicht durch den gewählten Studiengang beeinflusst werden. Im Beitrag werden Rohdaten aus einer Studie an der Universität Paderborn ( n = 121) genutzt, um eine fünfdimensionale Modellstruktur gegen eine eindimensionale zu testen und empirisch gestützte Argumente für eine mehrdimensionale Skalierung zu generieren. Durch Differential-Item-Functioning-Analysen wird geprüft, ob die Itemschwierigkeiten mit dem Merkmal ‚Studiengang‘ interagieren, sodass sie sich trotz gleicher Kompetenzausprägung für Untersuchungsteilnehmende beider Studierendengruppen signifikant unterscheiden und zu einer diagnostischen Verzerrung führen würden. Abschließend wird der beispielhafte Einsatz des Instrumentes im Rahmen einer Wirksamkeitsanalyse in Bezug die Effektivität des nordrhein-westfälischen Praxissemesters an der Universität Paderborn ( n = 26) dargelegt. Aus den differenzierten Ergebnissen werden unter anderem erste Hinweise auf Defizite in der Lehrerinnen- und Lehrerausbildung abgeleitet.
Keywords: Education

Effects of Teacher Feedback on Primary School Students’ Self-Efficacy Beliefs and their Interest in Science Lessons. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Influence of surface activation on the microporosity of PE‐CVD and PE‐ALD SiO x thin films on PDMS - Hoppe, Christian; Mitschker, Felix; Mai, Lukas; Liedke, Maciej Oskar; de los Arcos de Pedro, Maria Teresa; Awakowicz, Peter; Devi, Anjana; Attallah, Ahmed Gamal; Butterling, Maik; Wagner, Andreas; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Challenges in the interpretation of gas core levels for the determination of gas-solid interactions within dielectric porous films by ambient pressure XPS - de los Arcos de Pedro, Maria Teresa; Weinberger, Christian; Zysk, Frederik; Raj Damerla, Varun; Kollmann, Sabrina; Vieth, Pascal; Tiemann, Michael; Kühne, Thomas D.; Grundmeier, Guido (Applied Surface Science)
Keywords: Surfaces; Coatings and Films; Condensed Matter Physics; Surfaces and Interfaces; General Physics and Astronomy; General Chemistry

Comparative analysis of hexamethyldisiloxane and hexamethyldisilazane plasma polymer thin films before and after plasma oxidation - Xie, Xiaofan; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Plasma Processes and Polymers)
Keywords: Polymers and Plastics; Condensed Matter Physics

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen. Eine qualitative Studie über Informations- und Unterstützungsbedarfe von jungen Familien in Deutschland. - Wicker, Kathrin

Alltagsmanagement und Alltagskompetenzen von Familien in besonderen Lebenslagen - Wicker, Kathrin

Ausbildung in der zweiten Phase der Lehrerbildung. - Tenberge, Claudia (Professionalisierung von Grundschullehrkräften.)

Holz erleben. Technik verstehen. - Möller, Kornelia; Eikmeyer, Birgit; Tenberge, Claudia; Wilke, Torben; Zolg, Monika

Pre-Service Teachers’ Collaborative Lesson Planning and their Self-Concepts in Inclusive Education. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Schöpfen, gautschen, trocknen. Wassereinsatz in der Papierherstellung. - Tenberge, Claudia (Grundschule Sachunterricht.)

Theorien und Konzeptionen inklusiven Sachunterrichts - Schröer, Franz; Tenberge, Claudia (Inklusive (Fach-)Didaktik in der Primarstufe - Ein Lehrbuch)
Das Lehrbuch umfasst Beiträge zur Einführung in den Inklusionsdiskurs, zu Modellen der Allgemeinen Didaktik und der inklusiven Didaktik, zur praxeologischen Unterrichtsforschung, zum Mathematik-, Deutsch-, Sach-, Kunst-, Religions-, Englisch- und Sportunterricht sowie Kommentare zum Zusammenhang der aufgeführten Themenbereiche.

Future Primary Teacher Education: Computational Thinking and STEAM. - Lenke, Michael; Tenberge, Claudia

Über die Dächer der Welt. - Tenberge, Claudia (Grundschule Sachunterricht.)

Eine meta-analytische Untersuchung der Feedback-Related Negativity in motorischen Aufgaben - Faßbender, Laura; Krause, Daniel; Weigelt, Matthias

Sport Emotion Questionnaire (SEQ) – Nur ein Messinstrument zur Er-fassung wettkampfbezogener Emotionen oder kann der SEQ auch im Freizeit- und Gesundheitssport zum Einsatz kommen? - Thorenz, Kristin; Weigelt, Matthias

Mental rotation of tactic board instructions in basketball: Domain-specific expertise improves on-court performance - Krause, Daniel; Weigelt, Matthias

The affective response to moderate physical activity and relaxation exercises - Thorenz, Kristin; Sudeck, Gorden; Weigelt, Matthias

Trendbericht Organische Chemie 2022 - Andexer, Jennifer N.; Beifuss, Uwe; Brasholz, Malte; Breinbauer, Rolf; Breugst, Martin; Dumele, Oliver; Ernst, Martin; Ganardi, Ruth; Giese, Michael; Gulder, Tobias A. M.; Hüttel, Wolfgang; Kath‐Schorr, Stephanie; et al. (Nachrichten aus der Chemie)
Keywords: General Chemical Engineering; General Chemistry

Synthesis of Cyclic Carbonates Catalyzed by CaI2–Et3N and Studies on Their Biocatalytic Kinetic Resolution - Terazzi, Constanza; Laatz, Karoline; von Langermann, Jan; Werner, Thomas (ACS Sustainable Chemistry and Engineering)
Keywords: Renewable Energy; Sustainability and the Environment; General Chemical Engineering; Environmental Chemistry; General Chemistry

Synthesis of Bifunctional Phosphonium Salts Bearing Perfluorinated Side Chains and Their Application in the Synthesis of Cyclic Carbonates from Epoxides and CO 2 - Ren, Changyue; Spannenberg, Anke; Werner, Thomas (Asian Journal of Organic Chemistry)
Keywords: Organic Chemistry

Cover Feature: Impact of Heterocycle Annulation on NIR Absorbance in Quinoid Thioacene Derivatives (Chem. Eur. J. 23/2022) - Hou, Peng; Peschtrich, Sebastian; Huber, Nils; Feuerstein, Wolfram; Bihlmeier, Angela; Krummenacher, Ivo; Schoch, Roland; Klopper, Wim; Breher, Frank; Paradies, Jan (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Mental rotation with colored cube figures - Rahe, Martina; Weigelt, Matthias; Jansen, Petra (Consciousness and Cognition)
Keywords: Arts and Humanities (miscellaneous); Developmental and Educational Psychology; Experimental and Cognitive Psychology

Associations of chronotype and social jetlag with eating jetlag and their changes among German students during the first COVID-19 lockdown. The Chronotype and Nutrition study - Stutz, Bianca; Buyken, Anette; Schadow, A.M.; Jankovic, N.; Alexy, U.; Krueger, B. (Appetite)
Keywords: Nutrition and Dietetics; General Psychology

Relative validity of a glycemic index extended food-frequency questionnaire. - Goletzke, J; Weber, KS; Kössler, T; Zaharia, OP; Bódis, K; Müssig, K; Szendroedi, J; Burkart, V; Stutz, Bianca; Nöthlings, U; Buyken, Anette; Roden, M; et al. (Nutr Metab Cardiovasc Dis)

Technisches Lernen im Sachunterricht inklusiv gestalten - Fördert ein inklusionssensibles Seminar in der universitären Lehrerbildung das Interesse und die Selbstwirksamkeitserwartung von Bachelorstudierenden? - Schröer, Franz; Tenberge, Claudia (widerstreit Sachunterricht - Auf die Lehrkraft kommt es an? Professionalisierung von Lehrkräften für inklusiven Sachunterricht)

Entwicklung und Evaluation eines Fortbildungskonzepts im Kontext der technischen Bildung an Grundschulen am Beispiel von Lernrobotern - Janicki, Nicole (Technik: Verstehen wir, was wir nutzen!? - Tagungsband zur 23. Jahrestagung der Deutschen Gesellschaft für Technische Bildung in Mannheim vom 24.-25. September 2021.)
Keywords: technology education; teacher professionalisation; Computational Thinking; digitalization; learning robots

How to enable pre-service teachers to design technological teaching and learning inclusively? – On the nature and consideration of basic needs in teacher training - Schröer, Franz; Tenberge, Claudia (PATT39 - PATT on the Edge Technology, Innovation and Education)
Theoretical approaches to the transformation towards an inclusive educational system in Germany mostly agree on the involvement of developmental tasks in subject related research (Hinz, 2011). The common understanding of inclusion as a process geared towards equal participation of all children (Booth, 2012) requires a reflexive questioning of established values, attitudes and practices in order to develop inclusive subject related research, teacher training and teaching and learning (Pech & Schomaker, 2013). Among other things, this results in consequences for the design of pre- service teacher training. To a large extent, teacher education is driven by the promotion of central competencies, interests and self-efficacy (Baumert & Kunter, 2011). It aims towards the development and realisation of inclusive interdisciplinary science and social studies (‘Sachunterricht’) in primary education (Moser, 2018). In conjunction with largely acknowledged constructivist approaches to teaching and learning (Möller, 2001), the development of personality, the consideration of basic needs (Deci & Ryan, 1993) and promotion of individual potentials are repeatedly fundamentally represented in subject related and pedagogical considerations (Feuser, 1989; GDSU, 2013). Therefore, the aforementioned constructivist approach is connected to several certain key paradigms for teaching and learning processes (e.g., Vygotskij, 1978; Posner et al., 1982; van de Pol et al., 2010). In this regard, the nature of primary school students’ basic needs have empirically not been sufficiently studied yet. Theoretical frameworks from motivational psychology (Deci & Ryan, 1993) do not explicitly address how individual needs differ and how the diversity of needs can be included in joint-learning, multi-perspective technology education classes. The research project the present paper is part of aims to develop a research-based concept for the professionalisation of pre-service teachers in a seminar course. Therefore, the promotion of the pre- service teachers’ interests and self-efficacy expectations have been assessed in a pre-post research design with a control group visiting another course not related to technology education and inclusion. The present paper describes and discusses first results of the project and will give an outlook on subsequent developmental tasks.
Keywords: Inclusion; basic needs; pre-service teacher training; interest; self-efficacy

GDSU-Journal

(Selbst-)Einschätzungen zum Herausforderungsbereich Digitalisierung in Schule und Hochschule – Eine empirische Online-Befragung bei Sachunterrichtsstudierenden an der Universität Paderborn - Brenke, Laurien; Kirsch, Alexander; Blumberg, Eva (GDSU-Journal)

Effekte des Feedbacks von Lehrkräften auf die Selbstwirksamkeitsüberzeugungen und die intrinsische Motivation von Kindern im naturwissenschaftlichen Sachunterricht der Grundschule. Vortrag. 30. Jahrestagung der Kommission "Grundschulforschung und Pädagogik der Primarstufe" der Deutschen Gesellschaft für Erziehungswissenschaft (DGfE, Sektion Schulpädagogik). Thema: "Nachhaltige Bildung in der Grundschule" - Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva; Hellmich, Frank

Pre-service teachers’ team-teaching practices and children’s competence development in inclusive schools. Single Paper. EARLI SIG 11 Conference 2022 ‘Teaching and Teacher Education’. “Digital Transformation in Teaching and Teacher Education” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

DiPoSa: Didaktisch-diagnostische Potentiale des inklusionsorientierten Sachunterrichts: Identifizieren, Konzeptualisieren und Implementieren. Vortrag auf der Auftaktveranstaltung zur BMBF-Förderrichtlinie „Förderbezogene Diagnostik in der inklusiven Bildung“ im Rahmen des BMBF-Metavorhabens „Qualifizierung für inklusive Bildung“ - Schroeder, René; Blumberg, Eva; Miller, Susanne; Kottmann, Brigitte; Reh, Anne; Franzen, Katja

Technology Education in Elementary School Using the Example of 'Learning Robots' – Development and Evaluation of an In-Service Teacher Training Concept. - Janicki, Nicole; Tenberge, Claudia

Synthesis and Characterization of Catalytically Active Au Core─Pd Shell Nanoparticles Supported on Alumina - Feng, Yanyue; Schaefer, Andreas; Hellman, Anders; Di, Mengqiao; Härelind, Hanna; Bauer, Matthias; Carlsson, Per-Anders (Langmuir)
A two-step seeded-growth method was refined to synthesize Au@Pd core@shell nanoparticles with thin Pd shells, which were then deposited onto alumina to obtain a supported Au@Pd/Al2O3 catalyst active for prototypical CO oxidation. By the strict control of temperature and Pd/Au molar ratio and the use of l-ascorbic acid for making both Au cores and Pd shells, a 1.5 nm Pd layer is formed around the Au core, as evidenced by transmission electron microscopy and energy-dispersive spectroscopy. The core@shell structure and the Pd shell remain intact upon deposition onto alumina and after being used for CO oxidation, as revealed by additional X-ray diffraction and X-ray photoemission spectroscopy before and after the reaction. The Pd shell surface was characterized with in situ infrared (IR) spectroscopy using CO as a chemical probe during CO adsorption–desorption. The IR bands for CO ad-species on the Pd shell suggest that the shell exposes mostly low-index surfaces, likely Pd(111) as the majority facet. Generally, the IR bands are blue-shifted as compared to conventional Pd/alumina catalysts, which may be due to the different support materials for Pd, Au versus Al2O3, and/or less strain of the Pd shell. Frequencies obtained from density functional calculations suggest the latter to be significant. Further, the catalytic CO oxidation ignition-extinction processes were followed by in situ IR, which shows the common CO poisoning and kinetic behavior associated with competitive adsorption of CO and O2 that is typically observed for noble metal catalysts.
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Single-Layer T′ Nickelates: Synthesis of the La and Pr Members and Electronic Properties across the Rare-Earth Series - Wissel, Kerstin; Bernardini, Fabio; Oh, Heesu; Vasala, Sami; Schoch, Roland; Blaschkowski, Björn; Glatzel, Pieter; Bauer, Matthias; Clemens, Oliver; Cano, Andrés (Chemistry of Materials)
Understanding high-temperature unconventional superconductivity has become a long-lasting problem in which the cuprates stand as central reference materials. Given this impasse, the recent discovery of superconductivity in analogous nickelate thin films represents a fundamental breakthrough calling for the identification of additional materials in this class. In particular, thermodynamically more robust systems are required to “upgrade” nickelate superconductors from thin films to bulk samples. Here, we contribute in this direction by reporting the synthesis of the new single-layer T′ Pr2NiO3F compound, assessing this synthesis in relation to the only previous T′ nickelate La2NiO3F, and analyzing the electronic properties across the R2NiO3F series (R = La–Lu) via first-principles calculations. We find that these mixed anion systems have a comparatively high degree of stability and their synthesis enables a fine-tuning of their composition as inferred from their characterization. Furthermore, we find that these unprecedented square-planar nickelates hold great promise as prospective superconductors due to their exceptional electronic structure.
Keywords: Materials Chemistry; General Chemical Engineering; General Chemistry

Pseudo‐Octahedral Iron(II) Complexes with Near‐Degenerate Charge Transfer and Ligand Field States at the Franck‐Condon Geometry - Moll, Johannes; Naumann, Robert; Sorge, Lukas; Förster, Christoph; Gessner, Niklas; Burkhardt, Lukas; Ugur, Naz; Nuernberger, Patrick; Seidel, Wolfram; Ramanan, Charusheela; Bauer, Matthias; Heinze, Katja (Chemistry – A European Journal)
Keywords: General Chemistry; Catalysis; Organic Chemistry

Synthesis and characterization of multichromophoric iron(II) complexes as novel photosensitizers - Dierks, Philipp

Vielfalt stärken im naturwissenschaftlich-technischen Sachunterricht – Mehrperspektivische Sichtweisen zur Nutzung sprachlicher und kultureller Heterogenität im Sachunterricht der Grundschule und in der sachunterrichtsdidaktischen Lehrer*innenausbildung - Blumberg, Eva; Brenke, Laurien; Schürmann, Michelle; Gövert, André (Das Projekt "Vielfalt stärken")

Sachunterricht lehren in Zeiten der Pandemie – Eine Online-Befragung zu den Auswirkungen der digitalen Lehre auf den Materialeinsatz in der sachunterrichtsdidaktischen Hochschulausbildung - Thonemann, Lisa; Deutschen, Katrin; Lakemeyer, Jana Marie; Reh, Anne; Blumberg, Eva (GDSU-Journal)

Sachunterricht begründet planen – Das Prozessmodell Generativer Unterrichtsplanung Sachunterricht (GUS) - Tänzer, Sandra; Lauterbach, Roland; Blumberg, Eva; Grittner, Frauke; Lange, Jochen; Schomaker, Claudia (GDSU-Journal)

Effects of the composition of pre-service teacher teams on primary school students’ competencies in (non-)inclusive science lessons. Paper Presentation. EARLI SIG 15 Biennial Conference 2022 `Special Educational Needs´. “A Village to Teach a Child – The Influence of Contextual Factors on Learning and Development” - Hellmich, Frank; Hoya, Fabian Karl; Schulze, Jan Roland; Blumberg, Eva

Digitales Sachunterrichtsstudium in der Corona-Krise – Eine empirische Evaluationsstudie zur Rezeption des Unterstützungsangebots des Paderborner Lernzentrums „Sachunterrichtstreff“ bei Sachunterrichtsstudierenden im Grund- und Förderschullehramt - Deppe, Franziska; Reh, Anne; Blumberg, Eva (GDSU-Journal)

Effects on primary and secondary school students’ academic out-of-school learning experiences in Science Technology Engineering Mathematics (STEM) education. Single Paper. ECER (European Conference on Educational Research) 2022 PLUS. “Education in a Changing World: The impact of global realities on the prospects and experiences of educational research” - Schulze, Jan Roland; Crummenerl, Lena Luise; Sicking, Annika; Temmen, Katrin; Blumberg, Eva

Base Metal Iron(II)-Cobalt(III) Dyads for Photocatalytic Hydrogen Evolution - Huber-Gedert, Marina

Scalable Generation of Multiphoton Entangled States by Active Feed-Forward and Multiplexing - Meyer-Scott, Evan; Prasannan, Nidhin; Dhand, Ish; Eigner, Christof; Quiring, Viktor; Barkhofen, Sonja; Brecht, Benjamin; Plenio, Martin B.; Silberhorn, Christine (Physical Review Letters)
Keywords: General Physics and Astronomy

Inclusive science teaching in primary schools and its didactic-diagnostic potential. Single Paper. Porto International Conference on Research in Education 2022 (ICRE 2022) - Franzen, Katja; Blumberg, Eva; Schroeder, René; Reh, Anne; Miller, Susanne; Kottmann, Brigitte

Tuning of antifouling active PDMS domains tethered to epoxy/amine surface - Dogan, Deniz; Ruthmann, Simon; Seewald, Oliver; Bremser, Wolfgang (Progress in Organic Coatings)
Keywords: Materials Chemistry; Organic Chemistry; Surfaces; Coatings and Films; General Chemical Engineering

Reversible functionalization and exfoliation of graphite by a Diels–Alder reaction with furfuryl amine - Torkaman, Najmeh Filvan; Kley, Marina; Bremser, Wolfgang; Wilhelm, René (RSC Advances)
Furfuryl amine-functionalized few-layered graphene was prepared via a mechanochemical process by a [4 + 2] cycloaddition under solvent-free conditions.
Keywords: General Chemical Engineering; General Chemistry

“Red Carbon”: A Rediscovered Covalent Crystalline Semiconductor - Odziomek, Mateusz; Giusto, Paolo; Kossmann, Janina; Tarakina, Nadezda V.; Heske, Julian Joachim; Rivadeneira, Salvador M.; Keil, Waldemar; Schmidt, Claudia; Mazzanti, Stefano; Savateev, Oleksandr; Perdigón‐Toro, Lorena; Neher, Dieter; et al. (Advanced Materials)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Targeted Synthesis of the Type-A Particle Substructure from Enzymatically Produced Eumelanin - Büngeler, Anne; Kollmann, Fabian; Huber, Klaus; Strube, Oliver I. (Biomacromolecules)
Keywords: Materials Chemistry; Polymers and Plastics; Biomaterials; Bioengineering

COVID-19 in German Competitive Sports: Protocol for a Prospective Multicenter Cohort Study (CoSmo-S). - Niess, AM; Widmann, M; Gaidai, R; Gölz, C; Schubert, I; Castillo, K; Sachs, JP; Bizjak, D; Vollrath, S; Wimbauer, F; Vogel, A; Keller, K; et al. (Int J Public Health)

Video analysis of 100 matches in male semi-professional football reveals a heading rate of 5.7 headings per field player and match. - Weber, J; Ernstberger, A; Reinsberger, Claus; Popp, D; Nerlich, M; Alt, V; Krutsch, W (BMC Sports Sci Med Rehabil)

Classification characteristics of fine motor experts based on electroencephalographic and force tracking data. - Gaidai, R; Goelz, C; Mora, K; Rudisch, J; Reuter, EM; Godde, B; Reinsberger, Claus; Voelcker-Rehage, C; Vieluf, S (Brain Res)